2021
DOI: 10.1038/s41420-021-00410-6
|View full text |Cite
|
Sign up to set email alerts
|

PLAU directs conversion of fibroblasts to inflammatory cancer-associated fibroblasts, promoting esophageal squamous cell carcinoma progression via uPAR/Akt/NF-κB/IL8 pathway

Abstract: Cancer-associated fibroblasts (CAFs) plays an important role in the tumor microenvironment. The heterogeneity of CAFs affects the effect of CAFs on promoting or inhibiting tumors, which can be regulated by other cells in the tumor microenvironment through paracrine methods. The urokinase-type plasminogen activator (PLAU) system mediates cell proliferation, migration, adhesion, and other functions through the proteolytic system, intracellular signal transduction, and chemokine activation. PLAU promotes tumor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 49 publications
(84 reference statements)
3
32
0
Order By: Relevance
“…Remarkably, a recent study performed by Fang et al has revealed that PLAU could promote progression of ESCC tumor cell and that tumor cell-secreted PLAU could expedite the conversion of fibroblasts to inflammatory cancer-associated fibroblasts, accelerating the proliferation and migration of ESCC cells (69). Our study demonstrated that PLAU may serve as a prognostic biomarker of EAC, which warrants further exploration in future studies.…”
Section: Discussionsupporting
confidence: 68%
“…Remarkably, a recent study performed by Fang et al has revealed that PLAU could promote progression of ESCC tumor cell and that tumor cell-secreted PLAU could expedite the conversion of fibroblasts to inflammatory cancer-associated fibroblasts, accelerating the proliferation and migration of ESCC cells (69). Our study demonstrated that PLAU may serve as a prognostic biomarker of EAC, which warrants further exploration in future studies.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies have established the involvement of these six immune-related genes in invasion and metastasis of HNSCC tumor cells. More recently, both PLAU and STC2 were identified as oncogenes in HNSCC tumors, associated with immunosuppression and inflammation (Chang et al, 2003;Ieta et al, 2009;Na et al, 2015;Yang et al, 2017Yang et al, , 2020Joshi, 2020;Fang et al, 2021;Li et al, 2021). TNFRSF4 (also known as CD134/ OX40) is one of the representative targets of second-generation immune checkpoints, and its clinical efficacy has been observed by anti-TNFRSF4 (MEDI6469) therapy in HNSCC patients through regulating antigen-specific tumorinfiltrating T cells (Duhen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, the contribution of IYD in relation to HNF-family genes to tumorigenesis in the liver has not been investigated yet, and further studies are needed. HPR, PKLR and PLAU have been reported to be overexpressed in breast cancers and esophageal squamous cell carcinoma [ 69 , 70 , 71 ]. Conversely, our study showed the downregulation of those genes.…”
Section: Discussionmentioning
confidence: 99%